The current epidemiological status of urogenital schistosomiasis among primary school pupils in Katsina State, Nigeria: An imperative for a scale up of water and sanitation initiative and mass administration of medicines with Praziquantel. - Tolulope Ebenezer Atalabi; Stephen Dumebi Adoh; Kingsley Marvin Eze (Public Library of Science (PLoS), 2018)
Human schistosomiasis, a debilitating and chronic disease, is among a set of 17 neglected tropical infectious diseases of poverty that is currently posing a threat to the wellbeing of 2 billion people in the world. The SHAWN/WASH and MAM programmes in the study area require epidemiological data to enhance their effectiveness. We therefore embarked on this cross-sectional study with the aim of investigating the prevalence, intensity and risk factors of urogenital schistosomiasis.Interviewed 484 respondents produced terminal urine samples (between 10.00h - 14.00h) which were analyzed with Medi ─Test Combi 10 and centrifuged at 400 r.p.m for 4 minutes using C2 series Centurion Scientific Centrifuge. Eggs of S. haematobium were identified with their terminal spines using Motic Binocular Microscope. Data were analyzed with Epi Info 7. In this study, the overall prevalence and arithmetic mean intensity of the infection were 8.68% (6.39─ 11.64) and 80.09 (30.92─129.28) eggs per 10ml of urine respectively. Urogenital schistosomiasis was significantly associated with knowledge about the snail host (χ2 = 4.23; P = 0.0398); water contact activities (χ2 = 25.788; P = 0.0001), gender (χ2 = 16.722; P = 0.0001); age (χ2 = 9.589; P = 0.0019); economic status of school attended (χ2 = 4.869; P = 0.0273); residence distance from open water sources (χ2 = 10.546; P = 0.0012); mothers' occupational (χ2 = 6.081; P = 0.0137) and educational status (χ2 = 4.139; P = 0.0419).The overall prevalence obtained in this survey shows that the study area was at a low-risk degree of endemicity for urogenital schistosomiasis. Beneath this is a subtle, latent and deadly morbidity-inducing heavy mean intensity of infection, calling for urgent implementation of WHO recommendation that MAM with PZQ be carried out twice for School-Age Children (enrolled or not enrolled) during their primary schooling age (once each at the point of admission and graduation). The criteria for classifying endemic areas for schistosomiasis should also be reviewed to capture the magnitude of mean intensity of infection rather than prevalence only as this may underplay its epidemiological severity.